EFL STUDENTS’ PERCEPTIONS OF ONLINE LISTENING COURSES DURING THE COVID-19 PANDEMIC - Hasanah, Cindy Lestari; Purwanti, Indah Tri; Eliwarti, Eliwarti (Universitas PGRI Sumatera Barat, 2024)
This study aims to investigate the English Study Program students’ perceptions of online listening courses during the COVID-19 Pandemic at FKIP Universitas Riau. The subjects of this study were 89 students majoring in English Study Program in the academic year of 2020. This research is a mixed method study with explanatory sequential design. Researchers used surveys to collect quantitative data and were supported by qualitative data using interviews. For the research instrument, it was modified from Nurani and Widiati (2021) and Ha and Ngo (2021) with 32 items. The items were tested for their validity (r> r-table = 0.468) and reliability (r ≥ 0.80= 0.931). The results of the quantitative data in this study showed high average scores on students' perceptions of online listening courses involving the lecturer roles (3.11), courses (3.04), difficulty: technical section (2.98); the listening section (3.00) and the benefits (3.01). In line with that, the results of the qualitative data also show positive responses that students enjoyed online listening courses during the COVID-19 Pandemic despite having difficulties.